Design Principles for Serious Games Authoring Tool - Maxence Laurent; Sandra Monnier; Audrey Huguenin; Pierre-Benjamin Monaco; Dominique Jaccard (Serious Games Society, 2022)
Serious game development involves a multidisciplinary team of teachers and computer scientists. But the difference in computer competencies between the team members is a recurring difficulty in this collaboration. Authoring tools, which provide interfaces adapted to users' competencies, are promising solutions to overcome this difficulty. However, existing authoring tools are either limited in their functionalities (not powerful) or too complex for non-computer scientists (not usable). A comprehensive set of design principles to address this limitation does not yet exist. The objective of this research was to define a set of design principles for the development of powerful and usable authoring tools. To achieve this objective, we first defined a set of design principles. We then developed an authoring tool corresponding to these principles. Finally, we carried out test uses of that tool through the development of twelve serious games. Results show that this authoring tool enabled the development of a wide variety of serious games (powerful) by teams with heterogeneous computer skills (usable). Design principles defined in this research integrate and extend previous works. They allow to overcome the dilemma between the power and usability of authoring tools. This could unlock new possibilities for collaborative approaches in serious games developments.